Multidisciplinary Approach to Obesity : From Assessment to Treatment - Lenzi, Andrea; Migliaccio, Silvia; Donini, Lorenzo Maria (Springer International Publishing : Imprint: Springer, 2015)
This book describes in detail the multidisciplinary management of obesity, providing readers with a thorough understanding of the rationale for a multidisciplinary approach and with the tools required to implement it effectively. The emphasis is on a translational approach, starting from basic concepts and fundamental mechanisms of the pathology and clinical morbidity. Experts in the field discuss the full range of relevant topics, including the significance of physical exercise, psychological issues, nutritional strategies, pharmacological options, and bariatric surgery. Put another way, the book covers all aspects from the bench to the bedside. Physicians, scientists, and postgraduate students will all find it to be invaluable in understanding the causes and optimal management of obesity, which has rapidly become a major public health problem.